A study of the periodontal state of a late Medieval United Kingdom population. Issue 12 (December 2015) - Gonçalves, Pedro César Gaspar; Griffiths, Gareth; Rawlinson, Andrew
Highlights: Seventy five skulls were included in the study (12–60 years of age). Bone loss increased with age, but stabilized in older individuals (>45 years). The mean CEJ–AC distance varied from 2.1 mm to a maximum of 4.1 mm. Results were compared with a Roman–British population and XVIII century Londoners. Abstract: Objective: To study the severity of bone loss in a Medieval UK population, and compare this with other ancient UK populations from different time periods. Design: Skulls from a burial site in York (XI–XV century) were investigated. Skulls with a minimum of 17 teeth were included and were divided from childhood into five age groups. Direct measurements from the cement enamel junction (CEJ) to the alveolar crest (AC) were undertaken at six points around each tooth with a UNC 15 probe. The mean bone loss was calculated for each tooth type. Results: Seventy five skulls were included in the study (12–60 years of age). Bone loss was found to increase with age, but stabilized in older individuals (>45 years). The mean CEJ-AC distance varied from 2.1 mm in the youngest group to a maximum of 4.1 mm in 36–45 year olds. Results were compared with a Roman–British population (Whittaker et al., 1982) where comparable values for mean bone loss were 2.2 mm and 5.4 mm respectively, and a population of XVIII century Londoners (Whittaker et al., 1998) where bone loss of 1.1 mm and 4.0 mm was reported for the youngest and oldest age groups respectively. Conclusion: Measuring the CEJ–AC distance in dried skulls from ancient populations may be used as a proxy for the levels of periodontal disease irrespective of tooth wear. The findings from the current study suggest that the severity of periodontitis as determined by measurements of alveolar bone loss on dried skulls from this ancient population, seems to have declined in the United Kingdom from the III–V century to XVIII century. This may be due to changes in environmental factors including living conditions and diet, together with individual characteristics including systemic illness and genetic make up.